2000
DOI: 10.1002/1531-8249(200006)47:6<792::aid-ana12>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial neurogastrointestinal encephalomyopathy: An autosomal recessive disorder due to thymidine phosphorylase mutations

Abstract: Mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) is an autosomal recessive disorder defined clinically by severe gastrointestinal dysmotility; cachexia; ptosis, ophthalmoparesis, or both; peripheral neuropathy; leukoencephalopathy; and mitochondrial abnormalities. The disease is caused by mutations in the thymidine phosphorylase (TP) gene. TP protein catalyzes phosphorolysis of thymidine to thymine and deoxyribose 1‐phosphate. We identified 21 probands (35 patients) who fulfilled our clinical crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
170
0
7

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 316 publications
(178 citation statements)
references
References 45 publications
1
170
0
7
Order By: Relevance
“…The clinical manifestations of the few known MNGIE patients have been reviewed in detail [8,20,43]. Frequent findings in MNGIE ( > 70% of all cases in the series of Hirano et al [43]) that we observed in one or more of our patients were: cachexia, intestinal pseudo-obstruction, borborygmi, abdominal pain, diarrhoea, early satiety, abdominal cramps, nausea, vomiting, ptosis, ophthalmoparesis, polyneuropathy, and areflexia.…”
Section: Discussionmentioning
confidence: 63%
“…The clinical manifestations of the few known MNGIE patients have been reviewed in detail [8,20,43]. Frequent findings in MNGIE ( > 70% of all cases in the series of Hirano et al [43]) that we observed in one or more of our patients were: cachexia, intestinal pseudo-obstruction, borborygmi, abdominal pain, diarrhoea, early satiety, abdominal cramps, nausea, vomiting, ptosis, ophthalmoparesis, polyneuropathy, and areflexia.…”
Section: Discussionmentioning
confidence: 63%
“…The clinical diagnosis of MNGIE required the presence of six features as follows: 1) severe gastrointestinal dysmotility; 2) cachexia; 3) ptosis, ophthalmoparesis, or both; 4) peripheral neuropathy; 5) leukodystrophy on brain magnetic resonance imaging scan; and 6) laboratory evidence of mitochondrial dysfunction. As reported previously, we identified homozygous or compound heterozygous mutations in the TP gene in all 27 probands and heterozygous mutations in 22 relatives (7,9). Samples from three patients with diagnosis of autosomal dominant progressive external ophthalmoplegia, another disorder associated with multiple deletions of mtDNA, were also studied.…”
Section: Methodsmentioning
confidence: 77%
“…Clinically, MNGIE presents between the 1st and the 5th decades with ptosis, ophthalmoparesis, or both; skeletal myopathy; peripheral neuropathy; gastrointestinal dysmotility, manifesting as diarrhea and pseudo-obstruction; and cachexia (7). Clinical diagnostic tests typically reveal leukodystrophy on brain magnetic resonance imaging scans, lactic acidosis, and peripheral neuropathy with demyelination, axonal degeneration, or both.…”
mentioning
confidence: 99%
“…Additional manifestations include progressive external ophthalmoplegia, retinopathy, myopathy and diffuse leukoencephalopathy (present in all patients). All patients develop a sensorimotor demyelinating PNP but with varying degrees of severity, resulting in distal weakness and atrophy of the lower limb muscles [12]. Nerve biopsies performed in MNGIE patients disclosed demyelinating features, reduction of myelinated fiber density, and clusters of regenerating fibers.…”
Section: Multiple Deletions Of Mtdnamentioning
confidence: 97%